Critical and diverse role of alarmin cytokines in parasitic infections - Xing, Zhou; Liu, Suiyi; He, Xing (Frontiers in Cellular and Infection Microbiology, 2024)
Alarmin cytokines including IL-25, IL-33, and thymic stromal lymphopoietin (TSLP) function as danger signals to trigger host immunity in response to tissue injury caused by pathogenic factors such as parasitic infections. Parasitic diseases also provide an excellent context to study their functions and mechanisms. Numerous studies have indicated that alarmin cytokine released by non-immune cells such as epithelial and stromal cells induce the hosts to initiate a type 2 immunity that drives parasite expulsion but also host pathology such as tissue injury and fibrosis. By contrast, alarmin cytokines especially IL-33 derived from immune cells such as dendritic cells may elicit an immuno-suppressive milieu that promotes host tolerance to parasites. Additionally, the role of alarmin cytokines in parasite infections is reported to depend on species of parasites, cellular source of alarmin cytokines, and immune microenvironment, all of which is relevant to the parasitic sites or organs. This narrative review aims to provide information on the crucial and diverse role of alarmin cytokines in parasitic infections involved in different organs including intestine, lung, liver and brain.